Strategies for Handling Horizontal Conflicts Among Motorcycle Gangs in Bandung - M Faisal, Pebi Wahyudin; Setiawibawa, Rachmat; Setiawan, Bayu; Uksan, Arifuddin (Cita konsultindo, 2025)
The phenomenon of motorcycle gang violence in Bandung has developed into a multidimensional social conflict, rooted not only in direct acts of aggression but also in structural and cultural violence. This study analyzes the horizontal conflicts among motorcycle gangs using Johan Galtung’s violence triangle, Shaw and McKay’s social disorganization theory, and Friedrich Glasl’s conflict intervention framework. Employing Online Research Methods (ORM) and online content analysis, the research explores digital traces of gang-related violence, revealing how socioeconomic inequality, weak social cohesion, and cultural legitimization of violence contribute to the persistence of gang conflicts. The findings indicate that repressive law enforcement alone is insufficient, as conflicts have reached chronic levels of escalation. Lessons from Scotland’s Violence Reduction Unit and Costa Rica’s community-based prevention highlight the need for Indonesia to adopt a more holistic and participatory approach. The study recommends integrating law enforcement with preventive and transformative strategies, emphasizing education, youth empowerment, and community-based reconciliation to achieve sustainable conflict resolution.